Silver Nanoparticle-Decorated Tin Oxide Thin Films: Synthesis, Characterization, and Hydrogen Gas Sensing - Mohamedkhair, Amar K.; Drmosh, Q. A.; Yamani, Zain H. (Frontiers in Materials, 2019)
In this work, sputtered tin oxide films, decorated with silver nanoparticles were fabricated as hydrogen sensors. The fabricated thin films were characterized for their structural, compositional, morphological properties using various characterization techniques including X-ray photoelectron spectroscopy, UV-Vis absorption, X-Ray diffraction, field emission scanning electron microscope, and atomic force microscopy. The morphological characterization confirmed the formation of nanoparticles decorated SnO2 thin films. X-ray photoelectron spectroscopy spectroscopic analysis established the presence of silver/silver oxide on SnO2 thin films. The gas sensing properties of the fabricated sensors were investigated at different concentrations of hydrogen gas, over an operating temperature range of room temperature to 500 °C. It was found that the prepared sensor can detect a low hydrogen concentration (50 ppm) at high operation temperature, while the higher concentration (starting from 600 ppm) can be detected even at room temperature. Furthermore, on the basis of the electronic interaction between the SnO2 and the Ag nanoparticles, we propose a reaction model to explain the qualitative findings of the study.